2014
DOI: 10.1128/aac.01274-13
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Decapeptide OSIP108 Interferes with Candida albicans Biofilm Formation without Affecting Cell Viability

Abstract: We previously identified a decapeptide from the model plant Arabidopsis thaliana, OSIP108, which is induced upon fungal pathogen infection. In this study, we demonstrated that OSIP108 interferes with biofilm formation of the fungal pathogen Candida albicans without affecting the viability or growth of C. albicans cells. OSIP108 displayed no cytotoxicity against various human cell lines. Furthermore, OSIP108 enhanced the activity of the antifungal agents amphotericin B and caspofungin in vitro and in vivo in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 66 publications
3
36
0
2
Order By: Relevance
“…Furthermore, OSIP108 synergistically interacts with amphotericin B and caspofungin against mature C. albicans biofilms (14). A preliminary structure-activity relationship study of OSIP108 showed that (i) the order of amino acid residues is important for antibiofilm activity, as a scrambled version (S-OSIP108) containing all amino acids of OSIP108 but in a randomized order showed no antibiofilm activity, (ii) OSIP108 containing all amino acids in the D-configuration (D-OSIP108) still exhibits antibiofilm activity, and (iii) cyclization of OSIP108 is not favorable for its antibiofilm activity (14). In this follow-up study, we performed a whole amino acid scan of OSIP108, in which every amino acid of OSIP108 was individually replaced by all 19 other common amino acids (190 OSIP108 analogues).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, OSIP108 synergistically interacts with amphotericin B and caspofungin against mature C. albicans biofilms (14). A preliminary structure-activity relationship study of OSIP108 showed that (i) the order of amino acid residues is important for antibiofilm activity, as a scrambled version (S-OSIP108) containing all amino acids of OSIP108 but in a randomized order showed no antibiofilm activity, (ii) OSIP108 containing all amino acids in the D-configuration (D-OSIP108) still exhibits antibiofilm activity, and (iii) cyclization of OSIP108 is not favorable for its antibiofilm activity (14). In this follow-up study, we performed a whole amino acid scan of OSIP108, in which every amino acid of OSIP108 was individually replaced by all 19 other common amino acids (190 OSIP108 analogues).…”
mentioning
confidence: 99%
“…We previously identified the Arabidopsis thaliana-derived decapeptide OSIP108 (13), which specifically interferes with the biofilm formation process of C. albicans without affecting cell viability (14). The latter is an important characteristic to potentially limit the incidence of resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that OSIP108 can also inhibit formation of Candida albicans biofilms (Delattin et al, 2014c). C. albicans is the predominant human fungal pathogen and accounts for 35% of invasive fungal infections (Lewis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans cells can also grow as a surface-attached biofilm, e.g., on catheters and heart valves, thereby causing recurrent systemic infections (Cuéllar-Cruz et al, 2012;Mayer et al, 2013), which are in general resistant to most antimycotics (De Cremer et al, 2015;Delattin et al, 2014a). In the search for novel antibiofilm molecules, we previously identified OSIP108 as a new antibiofilm peptide (Delattin et al, 2014c). To get more insight into important amino acids that are linked to OSIP108's antibiofilm activity, we also performed a SAR using the same amino acid replacement scan (Delattin et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%